A Pediatric Telehealth Simulation for Prelicensure and Advanced Practice Nursing Students. Issue 6 (November 2021) - Ball, Sarah; Hanks, Jacquie; Potthoff, Meghan; Connelly, Susan
Abstract: Patients who are remote, underserved, or require specialized care services are not always able to seek appropriate care when necessary. Telehealth technology allows health care providers to connect virtually with their patients to provide safe and personalized care. To prepare future nurses and nurse practitioners for the use of technology, educators are responsible for integrating telehealth education into the curriculum. This article presents a clinical simulated approach that includes an interprofessional telehealth experience with prelicensure and nurse practitioner students within a pediatric focused simulation.